ANALISIS PELUANG USAHA CAFÃ‰ MENGGUNAKAN ANALISIS SWOT DALAM PENINGKATAN EKONOMI MASYARAKAT DI KECAMATAN PEUNARON ACEH TIMUR - Muhammad Yusuf Afredi; Sufi Sufi (Program Studi Administrasi Bisnis, 2023)
ABSTRACTThis research aims to find out how café businesses can improve the community's economy using SWOT analysis techniques. This research uses a qualitative research method with a descriptive qualitative approach. The data source used in this research is primary data source. Data collection was carried out by participant observation and interviews. Then the data will be analyzed using SWOT analysis. Based on the results of research conducted on cafés in Peunaron District, it was obtained that the strength of the café opportunity lies in its wide market share and has great opportunities in its business process. Meanwhile, the desain of the café and the culture of the Peunaron community are weaknesses and threats that must be faced in the café business process. Café businesses are able to help improve the community's economy through recruiting workers and business partners from home businesses with cafés which can increase sales from both business partners.